Postmodernism and the Puzzle of the Epistemological Relativism - Valantiejus, Algimantas (Sociologija. Mintis ir veiksmas, 2003)
This essay is an excerpt from the forthcoming book - Critical Discourse in Sociology. Between Positivism and Postmodernism. The essay deals with the dilemmas of relativism. The sociological concept of relativity of last decades was formulated as the integral part of sociological inquiry, aimed at the methodological complexity and some critical character of sociological thought. The intellectual transformation of recent sociology has been accompanied by a proliferation of alternative theories and concepts. Given the acute understanding of socially determined and arbitrary character of knowledge, the new sociological identity is being shaped by the pluralist context of latter-day sociological inquiry. This essay attempts an appraisal of differences in alternative modes of knowledge by exploring critically its various thematic features. As sociology‘s ongoing internal struggles continue, it is appropriate to ask whether the multidimensional approach is able to employ its own relativistic elements and maybe analytic techniques in the process of keeping itself more useful to the social sciences. It is possible to identify some postmodern trends in contemporary sociology that are becoming quite diverse internally. It is clear, however, that sociologists attach a little deal of significance to these differentiating changes as one of the crucial criteria of the arrival of new and the more complex forms of theorizing. Sociologists devote also too little attention to the relationship between contemporary social transformations and the restructuring some basic concepts in sociology. Furthermore, the current debates on relativism in sociology do not account for the fact that “postmodernism”, as a distinct and multiparadigmatic intellectual activity, is unequally distributed throughout the history of the social sciences.The paper examines the problematic relationship between positivistic and postmodern sociology, using the recent development of the social sciences in Lithuania as a case study and discussing the alternative models of sociology and their implications for intellectual reflexivity and critical reconstruction in social sciences. The dilemmas of relativism are clear in Lithuanian social scientists’s treatment of what they calls “postmodernism”. The aim of this essay is to explore the dual relations between the positivistic and postmodern trends in sociology by specifying the historical aspects of its contemporary development. As a consequence of one-sided, undifferentiating understanding of postmodernism, the more narrow, monist and “purist” concept of science is shaped. The central thesis is that pursuit of a „pure” science model restricts the potentiality of sociological enterprise. The paper argues specifically for the differentiation of the concept of postmodernism and suggests a need for sociology to more thoroughly integrate postmodern insights into its theory and practice while highlighting such key aspects of the sociological tradition as the need to ground its discoursive forms in dialogical, conventional and communicative attempts. The main goal of this paper is to demonstrate and make explicit some positive connections between explanatory and discursive forms of sociology examined from the perspective of critical social theory.
Keywords: postmodernism; epistemology; relativism; realism